Analisis Faktor Komitmen, Akademik, dan Kesejahteraan terhadap Sikap Mahasiswa PGSD terhadap Profesi Guru SD - Zahara Edlin Putri; Jesi Alexander Alim; Zakiah Ulya (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine how commitment, academic, and well-being factors influence the attitudes of Primary School Teacher Education (PGSD) students toward the teaching profession. The teaching profession plays a significant role in improving the quality of education in Indonesia, yet it is often perceived as less promising due to low welfare and heavy workloads. This research employed a descriptive quantitative method involving 30 PGSD students as respondents. Data were collected through a Likert-scale questionnaire distributed online via Google Form. The results show that most students have a positive attitude toward the teaching profession, with 37% in the moderate category, 33% in the high category, and 27% in the low category. In terms of specific factors, student commitment to the teaching profession mostly falls into the moderate category (53%), academic factors tend to be high (40%), while perceptions of teacher welfare are generally moderate to low (77%). These findings indicate that PGSD students generally have good appreciation and academic readiness for the teaching profession; however, their commitment remains unstable due to low welfare perceptions and limited social recognition. Efforts to improve teacher welfare and strengthen professional values through the curriculum are needed to foster students’ commitment and pride in pursuing a career as teachers.